Content Analysis of Geography Subject based on Olimpiade Sains NasionaL (OSN) Insenior High School of Padang City - Bayu Wijayanto; Dian Adhetya (Journal of Learning Improvement and Lesson Study, 2021)
Education in 21st century emphasizes the way of thinking HOTS (high Order Thinking Skill) to improve individual ability to survive in the face of global competition. HOTS learning is comprehensively tested in OSN (National Science Olympiad). Geography learning that is currently applied in Padang City does not fully have components that support 21st Century Education trends. The objective of this study is to identify material gaps tested in OSN with geography learning material in senior high schools of Padang City. The study was carried out using a descriptive qualitative approach, by analyzing the relationship between Geography syllabus content in OSN and geography learning content which applied in senior high schools of Padang City. The findings after the identification process are used as a basis to develop OSN-based learning supplements. The results of the study show that 29% of the class X geography content tested on OSN has not been included in learning content which has been applied in schools, especially physical geography. Practicum activities that should support cognitive aspects have not been well described in geographic content. Learning supplements have been compiled and focused on physical geography content, especially geomorphology and oceanography. Practicum modules are also to instill HOTS thinking and improve student skills that are useful in the era of intense utilization of geographic information systems. The expertise built through the modules that have been compiled includes mapping capabilities; investigative ability; and the ability to read, analyze, and interpret graphic data.